PERTANGGUNGJAWABAN PENYITAAN OLEH SATUAN POLISI PAMONG PRAJA DALAM PELAKSANAAN RAZIA PENERTIBAN PEDAGANG KAKI LIMA DI KOTA SAMARINDA - Risky Sektiadi (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACTStreet vendors (STREET VENDORS) is one of the perpetrators of the economic populist who is engaged in the informal sector trade efforts. The term five-foot stems from Netherlands colonial occupation where sidewalk width 150 cm or "five feet" so that the nickname. The rules regarding trading activity for the street vendors are already socialized. But street vendors being unconcerned and choose to trade in such a crowded place on the sidewalk, curb, on bridges, and other public facilities. So bring an impact on hygiene, facilities, and infrastructure, disruption of pedestrian and traffic flow, especially in the market town of Samarinda. This study raised the issue of reform and a barrier to action against sellers who trade what is prohibited in the city of Samarinda on the basis of the decision of the Mayor of number 19 the year 2001. . Research methods used in the writing of this thesis is the juridical sociological legal research that is being done to look at and examine how a real implementation rules. Data sourced from observations, interviews, a review of the literature, mass media, and other sources of support for research compilers. The results showed that action against street vendors based on the decision of the Mayor of number 19 the Year 2001 carried out according to the procedures or rules in force, be it from markets or Police Department of teachers ' Praja Samarinda. Keywords: Control, Forclosure, Street vendors